Executive Committee Minutes 2014-03-13 - Academic Senate:::::::::
Agenda – Approved. Minutes of 2/13 and 2/27 – Approved. Chair Report. President Report. Revision to the Communication Studies Program approved for Senate consent calendar. Statewide Senator Report. Vice Chair Report. APC and EPC reports read. FSAC Report. SAC Report. CFA Report. Senate agenda approved.